The Role of Discursive Traditions in Mesoamerican Historical Linguistics. An Inquiry on Colonial Nahuatl Wills - Mendoza Posadas, Mauro Alberto (2020)
Almost all colonial documentation of Mesoamerican languages was written on discursive models of European inspiration. In order to understand the relationship between the American languages and these models (or Discursive Traditions), and also to understand the theoretical implications, we made an analysis centered on the testamentary tradition to investigate the way these documents were translated to the sixteenth Century Nahuatl language. We particularly focused on the syntax-pargamatics interphase, so we could find the differences and similarities between the Discursive Tradition in Castilian and Nahuatl